Respuesta :
For this case we have the following expression:
[tex]-\frac{1}{4}(8 + 12) - (- 2 + 5)[/tex]
By definition, the distributive property states that:
[tex]a * (b + c) = ab + ac[/tex]
Applying this property to the given expression, we have:
[tex]-2-3 - (- 2 + 5)[/tex]
Likewise, the distributive property associated with the law of signs is applied, where:
- * - = +
- * + = -
+ * - = -
+ * + = +
[tex]-2-3 + 2-5[/tex]
Grouping:
[tex]-2-3-5 + 2[/tex]
Resolving:
[tex]-10 + 2 = -8[/tex]
Answer:
The steps were:
Distributive property
Distributive property with law of signs
Algebraic sum